Painless colonoscopy: fact or fiction? - Pieter Sinonquel; Alexander Jans; Raf Bisschops (Korean Society of Gastrointestinal Endoscopy, 2024)
Although colonoscopy is a routinely performed procedure, it is not devoid of challenges, such as the potential for perforation and considerable patient discomfort, leading to patients postponing the procedure with several healthcare risks. This review delves into preprocedural and procedural solutions, and emerging technologies aimed at addressing the drawbacks of colonoscopies. Insufflation and sedation techniques, together with various other methods, have been explored to increase patient satisfaction, and thereby, the quality of endoscopy. Recent advances in this field include the prevention of loop formation, encompassing the use of variable-stiffness endoscopes, computer-guided scopes, magnetic endoscopic imaging, robotics, and capsule endoscopy. An autonomous endoscope that relies on self-propulsion to completely avoid looping is a potentially groundbreaking technology for the next generation of endoscopes. Nevertheless, critical techniques need to be refined to ensure the development of effective and efficient endoscopes.